2021
DOI: 10.24294/jipd.v5i1.1242
|View full text |Cite
|
Sign up to set email alerts
|

Basic residential neighborhood infrastructure financing in Nigeria urban cities: Community development associations (CDAs)-based approach

Abstract: The study examined the community-based approach to finance basic public infrastructures in residential neighborhoods. The primary objectives of the study were to determine the condition of public infrastructures, the level of community engagement, the modalities of financing and the prominent influencing factors. The study adopted convenience sampling and questionnaire survey techniques. A total of 120 questionnaires were administered to residents of selected high-income communities (HICs) and low/medium-incom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…In certain high-income neighborhoods, waste seemed to be less of a factor in flooding, and more on the physical topography and building policies. However, it is important to note that overlaps exist in priority areas of flood management irrespective of the income levels of neighborhoods (Fateye et al, 2021). Aisha, an interview participant (Phone Interview, August 25, 2020), who lives in a high-income neighborhood confirmed this.…”
Section: Community-based Responses: Community Development Associationsmentioning
confidence: 87%
“…In certain high-income neighborhoods, waste seemed to be less of a factor in flooding, and more on the physical topography and building policies. However, it is important to note that overlaps exist in priority areas of flood management irrespective of the income levels of neighborhoods (Fateye et al, 2021). Aisha, an interview participant (Phone Interview, August 25, 2020), who lives in a high-income neighborhood confirmed this.…”
Section: Community-based Responses: Community Development Associationsmentioning
confidence: 87%
“…In response, some communities in Nigeria have created alternative institutions to meet their basic needs. For example, they organise and manage security and crime prevention (Ojebode et al 2016); are actively involved in the construction and maintenance of roads and basic health and education facilities (Oyalowo 2021); organise potable water (Fateye et al 2021) and waste collection and disposal (Wahab 2012); and provide other infrastructure.…”
Section: Olaniyanmentioning
confidence: 99%
“…These issues are not confined to Nigeria. Previous research has found that Africa's governance structures are typically top-down and elitist, with popular interaction and participation undervalued(Muna and Babamaragana 2021;Fateye et al 2021). AndMuna and Babamaragana's (2021) recent empirical findings from both Nigeria and Kenya demonstrate that policy and legal frameworks for actively engaging communities in governance are not backed by actual actions.…”
mentioning
confidence: 99%